Niat Resign di Tengah Burnout dan Karier Tanpa Arah - Salwa Nur Azizah; Diah Sofiah; Yanto Prasetyo (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract This study discusses the psychological conditions of employees related to career stagnation and work fatigue in the context of the intention to leave the job. The purpose of this research os to determine whether career plateau and burnout contribute to triggering turnover intention among employees. This study employeed a quantitative correlational design involing 169 employees of a private bank in Surabaya. The instruments used were the career plateau scale, burnout scale, and turnover intention scale. Data were analysed using Spearman Rho correlation. The findings indicate that career plateau and burnout have a positive relationship with turnover intention. These results highlight the importance of organizational attention to career development and psychological well- being as a preventive effort against employees’ intention to resign. Keywords: burnout, career plateau, employees, turnover intention Abstrak Penelitian ini membahas kondisi psikologis karyawan yang berkaitan dengan stagnasi karier dan kelelahan kerja dalam konteks niat untuk keluar dari pekerjaan. Penelitian ini bertujuan untuk mengetahui apakah career plateau dan burnout berperan dalam memicu turnover intention pada karyawan. Penelitian menggunakan desain kuantitatif korelasional dengan 169 karyawan bank swasta di Surabaya sebagai subjek. Instrumen yang digunakan meliputi skala career plateau, burnout, dan turnover intention. Teknik analisis data menggunakan korelasi Spearman Rho. Hasil penelitian menunjukkan bahwa career plateau dan burnout memiliki hubungan positif dengan turnover intention. Temuan ini menegaskan pentingnya perhatian organisasi terhadap pengembangan karier dan kesejahteraan psikologis sebagai langkah pencegahan terhadap niat keluar dari pekerjaan. Kata kunci: burnout, career plateau, karyawan, turnover intention